Analysis of the VCD protocol (bortezomib, cyclophosphamide, and dexamethasone) in the treatment of multiple myeloma (Research, Society and Development, 2023)
Multiple myeloma (MM) is an incurable cancer that affects plasma cells and represents the second most common type of blood cancer. Risk factors, such as exposure to substances like benzene, pesticides, and radiation, have been associated with the development of MM. In 2020, the World Health Organization recorded 176,404 new cases of MM worldwide, with 117,077 deaths related to the disease. In Brazil, approximately 2,600 cases were diagnosed between 2013 and 2019. The diagnosis of MM is based on the presence of monoclonal immunoglobulins, abnormal plasma cells in the bone marrow, and damage to target organs. The treatment of multiple myeloma is complex and often involves a combination of approaches, including chemotherapy, immunotherapy, radiotherapy, and, in certain cases, hematopoietic stem cell transplantation. Induction therapy with Bortezomib, cyclophosphamide, and dexamethasone (VCD) is often used and has shown rapid and effective results. It is worth noting that VCD is supplied free of charge within the Unified Health System (SUS). Bortezomib, a proteasome inhibitor, is an essential part of the treatment but was included in the National Commission for the Incorporation of Technologies in SUS (CONITEC) only in 2021, unlike the other components that have been part of the National List of Essential Medicines (Rename) since its first edition in 2001. This literature review aims to deepen the complexity and effectiveness of VCD therapy in the treatment of MM provided by SUS. The treatment of multiple myeloma is multifaceted, aiming to control the disease, alleviate symptoms, improve the quality of life, and extend the survival of patients, representing a significant challenge in the field of oncology.